Effects of an Adenosine A2A Receptor Antagonist on Striatal Dopamine D2-Type Receptor Availability: A Randomized Control Study Using Positron Emission Tomography - Okita, Kyoji; Kato, Koichi; Shigemoto, Yoko; Sato, Noriko; Matsumoto, Toshihiko; Matsuda, Hiroshi (Frontiers in Neuroscience, 2021)
Introduction: Altered dopaminergic neurotransmission, especially in the functioning of dopamine D2-type receptors, is considered central to the etiology of a variety of neuropsychiatric disorders. In particular, individuals with substance use disorders have been consistently observed to exhibit lower D2-type receptor availability (quantified as binding potential; BPND) using positron emission tomography (PET). Upregulation of D2-type receptor density thus may therefore provide a therapeutic effect for substance use disorders. Importantly, in vitro studies reveal that D2 receptors coexist with adenosine 2A (A2A) receptors to form the highest density of heteromers in the whole striatum, and there is a functional interaction between these two receptors. As such, blockade of A2A receptor’s function may prevent D2 receptor downregulation, yet no study has currently examined this hypothesis in humans. Methods and Analysis: This double-blind, randomized controlled trial aims to evaluate the effect of the A2A receptor antagonist istradefylline (compared to placebo) on both dopamine D2-type receptor availability in the human brain and on neuropsychological measurements of impulsivity. It is hypothesized that istradefylline will both increase striatal D2-type BPND and improve control of impulsivity more than placebo. Forty healthy participants, aged 20–65 with no history of psychiatric or neurological disorders, will be recruited and randomized into two groups and will undergo [11C]raclopride PET, once before and once after administration of either 40 mg/day istradefylline or placebo for 2 weeks. Neuropsychological measurements will be administered on the same days of the PET scans. Ethics and Dissemination: The study protocol was approved by the Certified Review Boards (CRB) of National Center of Neurology and Psychiatry (CR18-011) and prospectively registered with the Japan Registry of Clinical Trials (jRCTs031180131; https://jrct.niph.go.jp/latest-detail/jRCTs031180131). The findings of this study will be disseminated through peer reviewed scientific journals and conferences. Clinical Trial Registration:www.ClinicalTrials.gov, identifier jRCTs031180131.